2020
DOI: 10.1002/psp.2363
|View full text |Cite
|
Sign up to set email alerts
|

Where do immigrants move in Germany? The role of international migration in regional disparities in population development

Abstract: We examine the impact of foreign migration on regional disparities in population development in Germany by analysing spatial patterns and determinants at the county level for the period of 2007-2017. Counterfactual analyses show that international migration has been the major component of population growth across German regions. However, immigration has mainly been directed towards large cities and highly urbanised areas and has therefore reinforced the existing spatial disparities in population development. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 56 publications
(119 reference statements)
0
12
0
Order By: Relevance
“…The size of the specific citizenship population in the province of destination could be considered as a proxy of the network ' s role (Heider et al, 2020 ). A recent paper showed that the estimation of the gravity model, for Italian and foreign populations, provides a more accurate explanation of the role played by the different masses when the number of Italian and foreign populations are considered separately (Casacchia et al, 2019 ).…”
Section: Data and Me Thodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of the specific citizenship population in the province of destination could be considered as a proxy of the network ' s role (Heider et al, 2020 ). A recent paper showed that the estimation of the gravity model, for Italian and foreign populations, provides a more accurate explanation of the role played by the different masses when the number of Italian and foreign populations are considered separately (Casacchia et al, 2019 ).…”
Section: Data and Me Thodsmentioning
confidence: 99%
“…Foreigners, specifically Filipinos and Indians, hardly ever emigrate from provinces with a large population, as bigger populations indirectly represent many more job opportunities. The higher coefficient of the other populations of destination perfectly shows how large provinces attract foreigners who contribute to growing urbanization, as in many other European countries (Gans, 2017 ;Heider et al, 2020 ).…”
mentioning
confidence: 99%
“…However, we found some indirect evidence about impact on settlement type and attitudes towards immigrants after terrorist attacks. As shown by Heider et al (2020, p. 17), international migration is disproportionately directed at large cities and other highly urbanised areas. We investigated the interaction between type of settlement where the respondent resided and terrorist attacks (Models 9a and 9b, Table A6).…”
Section: Key Findingsmentioning
confidence: 97%
“…A second strand of literature focuses on demographic explanations, especially the selective migration of young adults and international migrants to large cities (Haase et al, 2010;Siedentop, 2018). Immigration is one of the main drivers of reurbanization, overcompensating for the out-migration of Germans in many cities and reinforcing spatial disparities of population change (Heider et al, 2020). However, the spatial preferences of migrants have changed significantly in recent years.…”
Section: Persistent Patterns Of Population Development In Germanymentioning
confidence: 99%
“…The region has also profited significantly from the international migration of both European Union (EU) citizens, especially from the new member states in central and eastern Europe, and late repatriates, i.e., German nationals with a Russian or Kazakh migration background (see Fig. 4 in Heider et al, 2020).…”
Section: Hot Spots Of Population Developmentmentioning
confidence: 99%